Design and Evaluation of UI/UX of Siwi Village Website in West Papua Province Using Cognitive Walkthrough - Prasetyo, Rahmat Ady; Inan, Dedi I.; Juita, Ratna; Sanglise, Marlinda; Baisa, Lorna Y. (Universitas Bandar Lampung (UBL), 2024)
This research aims to design the User Interface (UI) of the Siwi Village website, located in South Manokwari Regency, West Papua Province, and to evaluate its User Experience (UX). This is due to the numerous tourism potentials in the area that remain largely unknown to the public and hold significant economic potential. The UI/UX evaluation process was conducted using the Cognitive Walkthrough method. Figma was employed as a tool in the design process. During the evaluation phase, a questionnaire was constructed and tested by 35 respondents to assess user satisfaction with the UI. Although the overall evaluation results at this stage were quite satisfactory, the information regarding the village's tourism potential was found to be insufficiently highlighted. Therefore, a subsequent user experience evaluation was conducted involving 5 new users, utilizing the Cognitive Walkthrough method. The evaluation results using this method indicated high satisfaction levels in terms of Learnability (94 percent), Effectiveness (Quality rate 96 percent, Error rate 4 percent), and Efficiency (Time-Based Efficiency 0.016 goals/second or 1.6 percent), with an average task completion time of 8.74 seconds. Recommendations include the use of more attractive color combinations, the addition of feedback or suggestion boxes, and a click-to-enlarge image feature. This research is expected to contribute positively to the development of the Siwi Village website UI, resulting in higher user satisfaction levels.